Study Of The Process Of Cleaning Seedcotton - Yoldashev Khasanboy; Komiljon Abduraximov; Maftuna Inamova; Kamoldin Mirgulshanov (International Scientific and Current Research Conferences, 2021)
The quality of fiber depends on the amount of impurities in the seed cotton. The cleaning of seed cotton has a great impact on the quality of fiber. Therefore, the theoretical and practical study of the cleaning process leads to the production of quality fiber. If the cleaning process is applied to the fiber quality without theoretical and practical calculations, the quality of the fiber will deteriorate.